Penerapan Good Governance dalam Reformasi Birokrasi untuk Peningkatan Layanan Publik di Indonesia - Wirawan, Dinnur Garista; Tjenreng, Muhammad Baharuddin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study examines the implementation of good governance principles in bureaucratic reform to improve the quality of public services in Indonesia. Using a qualitative approach and literature review, the research explores key factors in principles such as transparency, accountability, public participation, innovation, and equity in building a more effective, efficient, and responsive public service system. The findings indicate that bureaucratic reform based on good governance can enhance public satisfaction, reduce corruption, and optimize the use of information technology in public services. However, significant challenges remain, including organizational culture resistance, disparities in access to technological infrastructure between urban and rural areas, and low human resource competence levels. The study recommends greater public participation, increased transparency through the use of information technology, human resource skill development, and the introduction of stricter monitoring systems. It is hoped that these findings will provide valuable insights for policymakers in implementing comprehensive and long-term bureaucratic reforms.